2018
DOI: 10.1016/j.neuropharm.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The α6 subunit-containing GABAA receptor: A novel drug target for inhibition of trigeminal activation

Abstract: Novel treatments against migraine are an urgent medical requirement. The α6 subunit-containing GABA receptors (α6GABARs) are expressed in trigeminal ganglia (TG), the hub of the trigeminal vascular system (TGVS) that is involved in the pathogenesis of migraine. Here we reveal an unprecedented role of α6GABARs in ameliorating TGVS activation using several pharmacological approaches in an animal model mimicking pathological changes in migraine. TGVS activation was induced by intra-cisternal (i.c.) instillation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 65 publications
(118 reference statements)
3
50
0
Order By: Relevance
“…Pre-clinical studies in migraine animal models have shown that topiramate inhibited neurogenic dural vasodilation by inhibiting CGRP release from pre-junctional trigeminal neurons induced by noxious inoculation (17, 51). We also found that topiramate inhibited CGRP immunoreactivity in the trigeminal ganglia and dura (23, 24) of rats in a capsaicin-stimulated migraine model (22). Topiramate has been also reported to enhance GABA currents of GABA A receptors, including the α6 subunit-containing GABA A receptors (α6GABA A Rs) (52).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pre-clinical studies in migraine animal models have shown that topiramate inhibited neurogenic dural vasodilation by inhibiting CGRP release from pre-junctional trigeminal neurons induced by noxious inoculation (17, 51). We also found that topiramate inhibited CGRP immunoreactivity in the trigeminal ganglia and dura (23, 24) of rats in a capsaicin-stimulated migraine model (22). Topiramate has been also reported to enhance GABA currents of GABA A receptors, including the α6 subunit-containing GABA A receptors (α6GABA A Rs) (52).…”
Section: Discussionmentioning
confidence: 64%
“…Topiramate has been also reported to enhance GABA currents of GABA A receptors, including the α6 subunit-containing GABA A receptors (α6GABA A Rs) (52). The α6GABA A Rs are highly expressed in trigeminal ganglia (23, 53) and were recently identified to be a novel drug target for migraine treatment (23). It remains to be elucidated whether the α6GABA A R-modulating effect of topiramate contributes to its antimigraine activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we mostly focused on receptors containing the α6-subunit, which have gained recent attention as potential novel future drug targets. α6-containing GABAA receptors have been reported to contribute to the alleviation of sensorimotor gating deficits (Chiou et al, 2018 ) and orofacial pain and migraine (Fan et al, 2018 ) in animal and cell models. Moreover, models of essential tremor and trigeminal neuropathic pain also have been demonstrated to benefit from drugs that act on α6-containing GABAA receptors (Handforth et al, 2018 ; Vasović et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that α6 subunits are recruited for the strengthening of synapses and added to α1 subunit containing postsynaptic densities (Accardi et al, 2015 ). Recent research has identified a number of putative pathophysiological roles which involve α6-containing receptors, and targeting these is considered an interesting strategy for disorders with sensorimotor gating deficits (Chiou et al, 2018 ), essential tremor (Handforth et al, 2018 ), and by way of receptors thought to be localized in the trigeminal ganglia, trigeminal neuropathic pain states (Puri et al, 2012 ; Vasović et al, 2019 ) and migraine (Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This peptide was found in ranging from approximately 35% to almost 50% neurons of the TG in rats and man, present in small-sized cells previously ( Lazarov, 2002 ). In capsaicin-treated rats, we found CGRP was densely distributed in TG neurons ( Fan et al, 2018 ). In contrast to the inhibition of TNC neuronal activation via GABA A receptors, whether VPA treats migraine is mediated by CGRP remains unclear.…”
Section: Discussionmentioning
confidence: 97%